2015
DOI: 10.1002/jhm.2336
|View full text |Cite
|
Sign up to set email alerts
|

We need to talk: Primary care provider communication at discharge in the era of a shared electronic medical record

Abstract: BACKGROUND: Poor communication between hospitalists and outpatient physicians can contribute to adverse events after discharge. Electronic medical records (EMRs) shared by inpatient and outpatient clinicians offer primary care providers (PCPs) better access to information surrounding a patient's hospitalization. However, the PCP experience and subsequent expectations for discharge communication within a shared EMR are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…Involving the patient in the decision to temporarily increase their opioid dose may improve patient‐perceived pain control . In addition, when possible, close communication between the hospitalist and the primary care physician may alleviate some of the uncertainty hospitalists feel when they prescribe an increased dose of chronic opioid therapy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involving the patient in the decision to temporarily increase their opioid dose may improve patient‐perceived pain control . In addition, when possible, close communication between the hospitalist and the primary care physician may alleviate some of the uncertainty hospitalists feel when they prescribe an increased dose of chronic opioid therapy …”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, when possible, close communication between the hospitalist and the primary care physician may alleviate some of the uncertainty hospitalists feel when they prescribe an increased dose of chronic opioid therapy. 39,40 Opioid prescribing practices by hospitalists were influenced by past negative experiences. This principle, defined as negativity bias, refers to the notion that in most situations, negative events are more salient, potent, and dominant than positive events.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of PCPs by Sheu et al indicated that for many discharges, information in addition to that present in the EHR was desirable to ensure a safe transition of care. 6 Two-way communication, such as with a phone call, allows for senders to verify information receipt and for receivers to ask questions to ensure complete information. To our knowledge, there have been no previous reports describing processes for improving verbal communication between hospitalist services and PCPs at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The use of telehealth was also regarded as a facilitator of actual nursing and as a barrier factor causing fear of changes in work. Both these subcategories were based on findings from the same studies (5,10,11,14,15,19). The nursing staff felt that the use of telehealth increases their job satisfaction (1), decreases the workload (5,12) and reduces stress (14,19).…”
Section: Synthesised Findingsmentioning
confidence: 99%